2013
DOI: 10.1111/tpj.12184
|View full text |Cite
|
Sign up to set email alerts
|

PIN6 is required for nectary auxin response and short stamen development

Abstract: SUMMARYThe PIN family of proteins is best known for its involvement in polar auxin transport and tropic responses. PIN6 (At1g77110) is one of the remaining PIN family members in Arabidopsis thaliana to which a biological function has not yet been ascribed. Here we report that PIN6 is a nectary-enriched gene whose expression level is positively correlated with total nectar production in Arabidopsis, and whose function is required for the proper development of short stamens. PIN6 accumulates in internal membrane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
98
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(100 citation statements)
references
References 57 publications
2
98
0
Order By: Relevance
“…By contrast, PIN5, PIN6, and PIN8 are characterized by a reduction in the middle hydrophilic loop, partially in PIN6 and more pronounced in PIN5 and PIN8. Surprisingly, localization studies revealed that PIN5, PIN6, and PIN8 predominantly localize to the endoplasmic reticulum (ER; Mravec et al, 2009;Dal Bosco et al, 2012;Ding et al, 2012;Bender et al, 2013;Sawchuk et al, 2013), although instances of plasma membrane localization of PIN5 and PIN8 have been reported as well (Ganguly et al, 2014). Auxin transport and auxin content measurements indicate that PIN5 likely mediates auxin transport into the ER lumen (Mravec et al, 2009), while PIN8 appears to counteract this activity, which is further supported by antagonistic genetic interactions observed between mutants and overexpressors of these two transporters (Ding et al, 2012;Sawchuk et al, 2013).…”
Section: Auxin Transport Across the Endoplasmic Reticulum Membranementioning
confidence: 96%
See 1 more Smart Citation
“…By contrast, PIN5, PIN6, and PIN8 are characterized by a reduction in the middle hydrophilic loop, partially in PIN6 and more pronounced in PIN5 and PIN8. Surprisingly, localization studies revealed that PIN5, PIN6, and PIN8 predominantly localize to the endoplasmic reticulum (ER; Mravec et al, 2009;Dal Bosco et al, 2012;Ding et al, 2012;Bender et al, 2013;Sawchuk et al, 2013), although instances of plasma membrane localization of PIN5 and PIN8 have been reported as well (Ganguly et al, 2014). Auxin transport and auxin content measurements indicate that PIN5 likely mediates auxin transport into the ER lumen (Mravec et al, 2009), while PIN8 appears to counteract this activity, which is further supported by antagonistic genetic interactions observed between mutants and overexpressors of these two transporters (Ding et al, 2012;Sawchuk et al, 2013).…”
Section: Auxin Transport Across the Endoplasmic Reticulum Membranementioning
confidence: 96%
“…PIN8, which is highly expressed in the male gametophyte, has an important role in pollen development and functionality (Dal Bosco et al, 2012;Ding et al, 2012), while PIN6 has been ascribed a function in the production of nectar and proper development of short stamens (Bender et al, 2013) as well as root growth and lateral root development (Cazzonelli et al, 2013). PIN5 appears to be necessary for fine-tuning of auxin function, as a pin5 mutant revealed only minor developmental phenotypes (Mravec et al, 2009).…”
Section: Auxin Transport Across the Endoplasmic Reticulum Membranementioning
confidence: 99%
“…28 Here the authors showed that PIN6 is required for a proper auxin response as pin6 mutants displayed an abnormal floral and nectary phenotype, exhibiting petals that fail to fully expand and significantly smaller nectaries (stamens) with reduced nectary production. Clearly, auxin is an important factor in the regulation of nectar production and the maturation of lateral nectarines.…”
Section: Pin6 Is Required For Proper Auxin Response During Root Develmentioning
confidence: 96%
“…Recent studies have identified transcription factors from the MYB family as regulators of nectar production in Arabidopsis (AtMYB57) and Nicotiana (NtMYB305) [58,59]. MYB305 has been shown to regulate nectarin production through NECTARIN genes [60] and starch accumulation during nectary development and thus the amount of nectar secreted [59].…”
Section: Manipulating Floral Rewardmentioning
confidence: 99%
“…Nectar secretion is also under the control of plant growth regulators jasmonic acid and auxin [58,61,62]. Downstream, the sugar transporter AtSWEET9 is involved in the export of sugars into the nectary [63**].…”
Section: Manipulating Floral Rewardmentioning
confidence: 99%